Introduction and Overview [In Agricultural R&D in the developing world] - Alston, Julian M.; Pardey, Philip G.; Piggott, Roley R. (International Food Policy Research Institute, 2006)
In the early 21st century, the science of agriculture has started to shift gears, just as it did 100 years ago. At the beginning of the 20th century, Charles Darwin’s theory of evolution, the pure-line theory of Wilhelm Johannsen, and the rediscovery of Gregor Mendel’s laws of heredity contributed to the rise of plant breeding, while Louis Pasteur’s germ theory of disease and the development of vaccines opened up lines of research in the veterinary sciences. The next epoch in agricultural technology will also have fundamental biological science at its foundation. Today, scientists armed with new molecular biologies involving genomics, proteomics, recombinant DNA, and supporting informatics technologies are delving deeper into the genetics of life, with potentially profound and pervasive implications for agriculture worldwide.